Origin and Nature of Green Clay Layers, ODP Leg 184, South China Sea - Tamburini, Federica; Adatte, Thierry; Föllmi, Karl B. (My University, 2012)
Green clay layers are reported from the Pliocene-Holocene intervals in five of the six sites drilled in the South China Sea (SCS) during Leg 184. Centimeter-scale discrete, discontinuous, and bioturbated layers, constituted by stiff and porous green clays, were observed, sometimes associated with iron sulfides and pyrite. Detailed mineralogical and geochemical analyses indicate that they differentiate from the host sediments in their higher content of iron, smectite, and mixed-layered clays and lower amounts of calcite, authigenic phosphorus, quartz, and organic matter. Although no glauconite was observed, the mineralogy and geochemistry of green clay layers, along with their geometrical relation to background sediments, suggest that they most likely represent the result of the first steps of glauconitization. Correlation between green layers and volcanic ash layers was suggested for green laminae observed elsewhere in Pacific sediments but was not confirmed at SCS sites. Statistical analysis of the temporal distribution of green layers in the records of the last million years suggests that green clay layers have become more frequent since 600 ka. Only at Site 1148 does the green layer record show a statistically significant cyclicity which may be related to orbital eccentricity. A possible influence of sea level variations, related both to climatic changes and tectonism, is postulated.